Analisis Kepuasan Pengguna Aplikasi DPS-Denpasar Prama Sewaka Menggunakan Metode End User Computing Satisfaction (EUCS) - Arditaloka, I Wayan Angga; Winardana, Made; Indrawan, Gede; Agus Oka Gunawan, Made (Jurnal PROCESSOR, 2025)
The rapid advancement of information technology has encouraged government institutions to adopt digital systems to enhance the effectiveness and efficiency of public services. This study examines user satisfaction with the DPS-Denpasar Prama Sewaka application, which serves as a platform for public complaints and information services in Denpasar City. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM), based on the End User Computing Satisfaction (EUCS) model. Data were collected from 100 randomly selected respondents. Five key variables were analyzed: content, accuracy, format, ease of use, and timeliness. The results indicate that collectively, these variables explain 75% of user satisfaction. However, only three variables-content (27.5%), ease of use (41.2%), and timeliness (29.7%)-have a significant individual impact. Accuracy and format were found to have no significant effect. These findings highlight the importance of improving information quality, accessibility, and prompt service delivery to enhance user satisfaction. The study provides practical recommendations for developers and local governments to refine digital public service systems that are more responsive and efficient in meeting community needs.